Determining the perceptions of selected GK-Laura residents on their interiors renovated by the UP BSID Class of 2011 a multiple case study on the role of interior design in socialized housing - Razon, Jehnarine Mhay T.; Faustino, Johanna Victoria A. (Quezon City College of Home Economics, University of the Philippine Diliman, 2015)
ABSTRACT The study aimed to determine the perceptions of selected residents of Gawad Kalinga-Laura on the interior design of their homes after they have been renovated by the UP BSID class of 2011. A multiple case study was applied wherein seven (7) residences pertaining to cases were evaluated through triangulation method with the used of (1) in-depth interviews, (2) surveys and (3) evaluation. The in-depth interviews and surveys that were obtained from the seven (7) respondents were used to determine the perceptions of the residents and to assess their behaviors based on the theory of housing adjustment. In addition, the study also aimed to prove the effectiveness of the renovation projects through the perceptions of the residents and the evaluation of the researcher to the changes that happened through time on the physical condition of the interiors. The findings indicate that most of the respondents have positive perceptions toward their renovated interiors. Also, the results displayed affirmative evaluations on the physical conditions of the interiors, thus, proving the effectiveness of the renovation project. However, during the four-year period, the respondents acknowledged their dissatisfaction on their spaces thus producing deficits. Hence, the residents developed certain adjustment behaviors to remove this deficits, specifically, (1) re-arranging the layout of the furniture and (2) adding different design elements on the interiors. In conclusion, the enhancement of the interiors through the renovation project of the UP BSID class of 2011, not only contributed to the improvement of the residents' lifestyle and welfare but also increased the residents' self-esteem and appreciation on their interiors. More importantly, the project has demonstrated that the benefits provided by interior design are not only for the elite but also for the low-income class.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Welfare recipients -- Housing -- Philippines -- Renovation